Acetabulum fractures in elderly: A systematic review of fracture pattern and treatment - Goyal, Tarun (J Clin Orthop Trauma, 2020)
PURPOSE: Acetabulum fractures are being increasingly seen with low impact injuries in elderly patients. This article aimed to study systematically literature on geriatric acetabulum fractures. Objectives of this systematic review were to study (1) demography of patients, common mechanisms of injury and types of fracture patterns commonly seen in elderly patients, (2) treatment used for these fractures in literature and (3) mortality rates in elderly with these fractures. METHODS: Systematic search was carried out in May 2020 using predefined search strategy for all studies published in the English language in last 20 years. Literature search and data abstraction was done by two independent reviewers. RESULTS: After screening of all abstracts, a total of 48 studies were included in the systematic review. In total there were 7876 geriatric patients with acetabulum fractures. Mean age of the patients was 72.47 years. There were 4841 males (61.5%). Fall from low heights was the most common mechanism of injury, present in 47.12% patients followed by motor vehicular accidents in 28.73%. Most common fracture pattern was both column fracture, seen in 19.03% patients, followed by anterior column and posterior hemitransverse fracture in 17.23%, anterior column fractures in 17.13%, and posterior wall fractures in 13.46% patients. Out of total 5160 patients for whom details of treatment were available, 2199 (42.62%) were given non-operative treatment, 2285 (44.28%) were treated with ORIF of acetabulum fracture, 161 (3.12%) were treated with percutaneous fixation and 515 (9.98%) were treated with primary THA. Gull sign, femoral head injury and posterior wall comminution were associated with poorer prognosis after ORIF and may form an indication for a primary THA. CONCLUSION: Literature on treatment of geriatric acetabulum fractures is not enough to draw any definite conclusions. There is limited evidence from current literature that surgery could be considered a safe treatment option for displaced acetabulum fractures in elderly. Primary THA can provide early mobility and reduce chances of resurgery in fracture patterns where restoration of joint surface may not be possible.